Ascorbic acid, carotenoid contents and antioxidant properties of Australian summer carrot with different irrigation amounts on a free-draining, sandy soil - Ludong, D.; Nio, S.; O Malley, P.; Singh, Zora; Gibberd, Mark (Innovative Scientific information and Services Network, 2017)
It is important to reduce the use of water for agricultural production in response to water scarcity and environmental concerns. The nutritive value in fruits and vegetables including carrot (Daucus carota L.), can be influenced by various climatic conditions, such as light intensity, temperature, and irrigation. The effect of differential irrigation treatments on the contents of ascorbic acid and carotenoid as well as antioxidant properties (antioxidant content, antiradical power, and antioxidant capacity) were studied in carrot (cv. Stefano) roots grown on a free-draining, sandy soil (Grey Karrakatta Sand) in the summer period. This soil has water holding capacities as low as 10-13% and requires irrigation up to 150% of class A pan evaporation (Epan) to optimize growth and quality. The irrigation treatments applied in this study consisted of 100% Epan replacement, 150% Epan replacement and crop factor. The soil water stress index calculation showed the soil water tension ranged from -2.4 to -7.6 kPa that was within the range between saturation and field capacity for sandy soil. The reduction of irrigation amount from 150% to 100% Epan did not differentiate the contents of ascorbic acid and total carotenoid, but it slightly decreased antioxidant properties of carrot grown in the free draining sandy soil.